The dynamics of heavy metals content in water Belaya river on the territory of Beloretsk district, Republic of Bashkortostan (Eurasian Journal of Ecology, 2016)
Examine the contents of heavy metals in the water of the river Belaya in the territory of Beloretsk district, Republic of Bashkortostan. Identified the excess of average annual concentrations of Cu, Zn, Fe, Mn respect to the prescribedlimit values.
Keywords: water; river Belaya; maximum allowable concentration; clark; copper; zink; iron; manganese; nickel; cobalt; lead; cadmium.